Low pressure chemical vapor deposition synthesis of large area hetero-doped mono- and few- layer graphene with nitrogen and oxygen species. (22nd February 2019) - Hasan, Maria; Meiou, Wang; Yulian, Liu; Ta, Huy Q; Zhao, Liang; Mendes, Rafael G; Oswald, Stefan; Akhter, Zareen; Malik, Zahida P; Ahmad, Nasir M; Liu, Zhongfan; Rümmeli, Mark H
Abstract: The doping graphene helps breaks its surface inertness providing it an intrinsic degree of catalytic activity. While single elemental doping of graphene (e.g. with N) enhances its catalytic potential, the current trend is to develop graphene doped with multiple elements. These heterodoped graphene species have improved electro-catalytic activities as compared to their corresponding single heteroatom doped counterparts because of strong charge redistribution and synergistic effects due to differences in the dopant electro-negativities. Hence, they are better suited for multiple catalytic reactions to better cope with reaction intermediates. Never-the-less, to date only a few examples exist. In this work we show it is possible to synthesize in a single CVD step, large area single- and few- layer graphene doped with oxygen and nitrogen species. Moreover, this is achieved using a solid precursor in a pure H2 environment with growth being achieved in under 5 min.